Virtual Soil Information Systems in the Bihar Subregion and at Tedej Corp - Takács, Péter; Tamás, János; Lénárd, Csaba (Acta Agraria Debreceniensis, 2004)
After evaluating the sample sites’ soils and environmental status, we built up 2 different soil information systems. The first relies on analog data (soil maps), and is based on a regional model; its sample site is the Bihar sub-region. The second is a complex, field scale virtual 3D system, based on several types of data sources. (Aerial photos, GPS, field samples, hyper and multispectral images, soil maps). In this paper, we analyze and evaluate these systems. The greatest advantage of the models is that, with their usage, we can reveal connections which cannot be made by analyzing the individual elements of our data sources. We discovered that with the help of our systems, the monitoring and evaluating of the processes taking place in the soil is more fast and simple.